Understanding of Perceived Gender Discrimination Phenomenon among Women in the Pakistani Context - Sadia Zaman; Irum Naqvi (NUST Journal of Social Sciences and Humanities, 2022)
The present research was planned for qualitative exploration of perceived gender discrimination in the Pakistani context on the lines of relative deprivation theoretical background. Five focus group discussions (N = 35) with working, non-working, married, and single adult women and two in-depth interviews with gender rights social activist and female lawyer were conducted. Their age range was 22-40 years with a mean age of 28.56 years. Content analysis technique revealed eight distinct domains as the main categories of discrimination perceived by women on the basis of gender, namely, education, employment/career, familial matters, financial matters, general social rights, appreciation and encouragement, abuse and violence, and gender-based stereotyping. Participants reported that despite offering more sacrifices and compromises, as compared to men the subsequent appreciation and encouragement given to them is non-existent. This contributed to one of the important and unique themes of perceived discrimination.